The other valley : a novel [large type] - Howard, Scott Alexander (Thorndike Press large print top shelf., 2024)
"Sixteen-year-old Odile is an awkward, quiet girl vying for a coveted seat on the Conseil. If she earns the position, she'll decide who may cross her town's heavily guarded borders. On the other side, it's the same valley, the same town. Except to the east, the town is twenty years ahead in time. To the west, it's twenty years behind. The towns repeat in an endless sequence across the wilderness. When Odile recognizes two visitors she wasn't supposed to see, she realizes that the parents of her friend Edme have been escorted across the border from the future, on a mourning tour, to view their son while he's still alive in Odile's present. Edme--who is brilliant, funny, and the only person to truly see Odile--is about to die. Sworn to secrecy in order to preserve the timeline, Odile now becomes the Conseil's top candidate. Yet she finds herself drawing closer to the doomed boy, imperiling her entire future"--